Online inventory booking system (Sistem Inventory PTJPP) for Pejabat Tanah dan Jajahan Pasir Puteh / Siti Noorhaslinda Mohamed Ameri - Mohamed Ameri, Siti Noorhaslinda (Bachelor of Science in Information System Management (Hons.), 2013)
This paper discusses the information system development for Pejabat Tanah Dan Jajahan Pasir Puleh (PTJPP) 1o manage the inventory system as well as to solve the problems arising from the use of manual system. The inventory system has been named as "Sistem inventory PTJPP" and the function of the system is to manage the inventory system that manages the booking approval of the items made by the stafs and management the movement of inventory equipment. This system was provided with user-friendly menu and interface design and also easy to be used by PTJPP staff. The "Sistem Inventory PTJPP" was developed in stages and has been following all SDLC process as well as used PHP language as source code, text, graphic and animation designs. To create the system database for saving and retrieving the related data, MySQL was used. The benefit of the system is to solve the problem faced by PTJPP in managing inventory system through the manual process used before. The process of the storing, managing, searching, and retrieving the information of inventory become easily, quickly and securely by using the "Sistem Inventory PTJPP".